Enhancing Executive Control: Attention to Balance, Breath, and the Speed Versus Accuracy Tradeoff - Singh, Varsha; Mutreja, Vaishali (Frontiers in Psychology, 2020)
Malleability of executive control and its enhancement through yoga training is unclear. In Study 1, participants (yoga group; n = 27, mean = 23.27 years) were tested on executive control tasks pre and post 8 weeks of yoga training. The training focused on attention to postural control during yoga asanas and respiratory control during pranayama-breathing (30 min each of postural and breath-control training, biweekly). Yoga training was assessed via performance ratings as to how well a posture was executed and by examining errors that reflected inattention/failures in postural and breath control. We also explored whether attentional demands on motor and respiratory control were associated with three components of executive control (working memory, cognitive flexibility, and inhibition) during nine executive control tasks. Partial correlation results revealed that the three components of executive control might be differentially impacted by postural and breath control, and selectively associated with either speed or accuracy (except for cognitive flexibility). Attentional demands influenced the link between postural, breath, and cognitive control. In Study 2, comparisons between a yoga group and a gender-matched control group (control group; n = 27, mean = 23.33 years) pointed towards higher working memory accuracy and a better speed-accuracy tradeoff in inhibitory control in the yoga group. A ceiling-practice effect was addressed by examining yoga practice learning (i.e., practice-induced change in postural and breath control reflected in ratings and errors) on executive control performance across two sets of tasks: repeatedly tested (pre and post-8 weeks) and non-repeatedly tested (post-8 weeks). Attention to motor and respiratory control during yoga might be considered as a potential mechanism through which specific components of executive control in young adults might be enhanced potentially via altering of speed-accuracy tradeoff.